Tailoring CSR strategy to company size? - Alexandra Zbuchea; Florina Pînzaru (Management dynamics in the knowledge economy, 2017)
Corporate Social Responsibility (CSR) is one of the most debated topics in the academic and professional business literature, being analyzed in a myriad of perspectives, from philosophy, to marketing, management practice, managerial strategies or financial impact. The very term of CSR implies that involving with society in a structural way that is part of a business DNA is or should be understood as a characteristic of big size companies (e.g. corporations). Academic literature and financial reports show a direct relationship between a company size and its CSR budget, therefore some conclusions have been taken that CSR is effective mostly in cases of big budgets and, consequently, of big companies. Academic research also tends to favor large corporations. Most of the literature on CSR is dedicated to large companies. Nevertheless, in the past decade, increasingly more studies have investigated the social responsibility assumed by other types of companies (such as SMEs), by public institutions or by nonprofit organizations. Our present empirical analysis based on structured academic literature review (comprehensive selection of relevant international papers and content analysis) demonstrates that CSR should go beyond the classical understanding of the corporation concept and that it should be tailored to SMEs as well. Innovation and top management support are the drivers of effective CSR adoption by SMEs, for positive results meeting specific business model requirements, as well as for society. Going beyond social responsibility as a philosophical duty, correctly tailored CSR strategies can be efficient for small and medium enterprises in meeting strategic business objectives.
10.25019/MDKE/5.3.06; 10.25019/MDKE/5.3.06; 2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920